1976
DOI: 10.2307/2335091
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Order of an Autoregressive Model by Akaike's Information Criterion

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Biometrika Trust is collaborating with JSTOR to digitize, preserve and extend access to Biometrika. SUMMARYThe asymptotic distribution is obtained of the order of regression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 5 publications
(7 reference statements)
0
115
0
Order By: Relevance
“…This has to be done to mitigate non-consistent estimation and increased variance [26]. The AR model was run for model order numbers in the range of 45 to 65 with the increment of 10.…”
Section: Effect Of Changing Model Ordermentioning
confidence: 99%
“…This has to be done to mitigate non-consistent estimation and increased variance [26]. The AR model was run for model order numbers in the range of 45 to 65 with the increment of 10.…”
Section: Effect Of Changing Model Ordermentioning
confidence: 99%
“…Several criteria are used for this purpose, such as Akaike information criterion (AIC) [9,10], Bayesian information criterion (BIC) [11] and the Hannan-Quinn information criterion (HQ) [12,13]. Considering the limitations of AIC and BIC criteria, in this paper, the number of the nearest neighbor points is calculated by HQ information criterion.…”
Section: Lsvm-hq-sax-dtw-k Algorithmmentioning
confidence: 99%
“…This extra penalty term makes CL-AIC in favour of smaller K compared to AIC given the same data set. It has been shown that AIC tends to over-fit by both theoretical [7,13] and experimental studies [21,11]. The extra penalty term in CL-AIC thus has the effect of rectifying the over-fitting tendency of AIC.…”
Section: Completed Likelihood Akaike's Information Criterion (Cl-aic)mentioning
confidence: 99%